Comparison of Diagnostic Efficacy of [68Ga]Ga-FAPI-04 and [18F]FDG PET/CT for Staging and Restaging of Gastric Cancer - Zhang, Shumao; Wang, Wei; Xu, Tingting; Ding, Haoyuan; Li, Yi; Liu, Huipan; Huang, Yinxue; Liu, Lin; Du, Tao; Zhao, Yan; Chen, Yue; Qiu, Lin (Frontiers in Oncology, 2022)
Purpose: This study aimed to compare the potential diagnostic efficacy of gallium68-fibroblast-activation protein inhibitor ([68Ga]Ga-FAPI-04) and fluorine18-fluorodeoxyglucose ([18F]-FDG) positron emission tomography-computed tomography (PET/CT) for primary tumors, lymph nodes, and distant metastatic lesions of gastric cancer (GC), and to explore the effects of [68Ga]Ga-FAPI-04 and [18F]-FDG on tumor staging and restaging in GC. Methods: This single-center retrospective study (NCT2100044131) was conducted at the Affiliated Hospital of the Southwest Medical University between June 2020 and December 2021. Images of patients with GC who were pathologically confirmed and underwent contemporaneous [18F]-FDG and [68Ga]Ga-FAPI-04 PET/CT within 1 week were analyzed. The diagnostic efficacy of [68Ga]Ga-FAPI-04 PET/CT and [18F]-FDG PET/CT for TNM staging of GC was compared using ﻿McNemar test. The maximum standard uptake value (SUVmax) of each lesion in the two imaging types was compared using the Mann-Whitney U test. Results: In total, 25 patients with GC (mean age, 56±12 years) were evaluated. [68Ga]Ga-FAPI-04 PET/CT exhibited higher sensitivity compared to [18F]-FDG PET/CT for detecting primary tumors (18/19 [94.74%] vs. 13/19 [68.42%], χ2=6.866, P < 0.01), lymph node metastasis (75/77 [97.40%] vs. 32/77 [41.56%], χ2=2.888, P =0.089), and distant metastases (275/283 [97.17%] vs. 122/283 [43.11%], χ2=11.858, ﻿ ﻿P < 0.01). ﻿[68Ga]Ga-FAPI-04 accumulation was significantly higher than that of [18F]FDG in tumors (median SUVmax, 10.28 vs 3.20; U=59.00, P < 0.01), lymph node metastasis metastases (median SUVmax, 9.20 vs 3.15; U=53.50, P < 0.01) , and distant metastases (median SUVmax, 8.00 vs 4.20; U=200.00, P < 0.01). Compared to [18F]-FDG PET/CT, [68Ga]Ga-FAPI-04 PET/CT resulted in new oncological findings in 14/25 patients and up-regulated tumor staging or restaging in 5/25 patients. Conclusion: Our preliminary results regarding the impact of [68Ga]Ga-FAPI-04 PET/CT on tumor staging highlight the potential of this approach for increasing the accuracy of GC diagnosis, which may facilitate treatment decision-making.